2003
DOI: 10.1289/ehp.111-1241504
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and proteomic profiling of responses to toxic metals in human lung cells.

Abstract: Examining global effects of toxic metals on gene expression can be useful for elucidating patterns of biological response, discovering underlying mechanisms of toxicity, and identifying candidate metal-specific genetic markers of exposure and response. Using a 1,200 gene nylon array, we examined changes in gene expression following low-dose, acute exposures of cadmium, chromium, arsenic, nickel, or mitomycin C (MMC) in BEAS-2B human bronchial epithelial cells. Total RNA was isolated from cells exposed to 3 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(68 citation statements)
references
References 47 publications
6
61
1
Order By: Relevance
“…A similar observation was reported following arsenic exposure in a human lung cell line. At low concentrations, the arsenic response was distinct but a higher dose caused a very different gene expression profile composed of mostly general stress response genes (12). Another study in rainbow trout fry reported similar gene expression profiles in response to high doses of four different toxicants ( -naphthoflavone ( NF), Cd, CCl4, and pyrene).…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was reported following arsenic exposure in a human lung cell line. At low concentrations, the arsenic response was distinct but a higher dose caused a very different gene expression profile composed of mostly general stress response genes (12). Another study in rainbow trout fry reported similar gene expression profiles in response to high doses of four different toxicants ( -naphthoflavone ( NF), Cd, CCl4, and pyrene).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, it has been reported that carcinogenic metals including Cd and Ni exhibited different patterns of gene expressions and had different carcinogenic mechanisms [Bartosiewicz et al, 2001;Andrew et al, 2003]. Hence, the gene alterations that were considered to be associated with carcinogenesis have not been shown directly.…”
Section: Discussionmentioning
confidence: 99%
“…Bartosiewicz et al [2001] have shown that cadmium chroride, Benzo[a]pyrene, and trichloroethylene exhibited different patterns of gene expression in the livers of exposed mice. Likewise, Andrew et al [2003] reported that cadmium chloride, sodium dichromate, and nickel subsulfide altered only a few genes that overlapped with DNA-cross-linker mitomycin C in human lung cells. Thus, these metals induced quite different gene expression patterns from the ones genotoxic and nongenotoxic carcinogens did, indicating a different class of carcinogen.…”
Section: Introductionmentioning
confidence: 97%
“…The c-Jun N-terminal kinase (JNK) is selectively activated in A549 cells by 10 μM Cr(VI), and pre-exposure of cells to N-acetylcysteine prevents this activation [68]. This level of Cr(VI) is also sufficient to alter the expression of dozens of genes [88] and to induce apoptosis in BEAS-2B (normal human bronchial epithelial) cells [89], and it causes extensive cell death in primary human fibroblasts [90].…”
Section: Discussionmentioning
confidence: 99%